2018
DOI: 10.3390/app8122551
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Petroleum Hydrocarbons Degradation by Klebsiella pneumoniae and Pseudomonas aeruginosa

Abstract: : The aim of this work was to develop bacterial communities to effectively degrade petroleum hydrocarbons (PHs). We investigated the biotic and abiotic contributors to differences in PHs degradation efficacy between two bacterial strains, Klebsiella pneumoniae (Kp) and Pseudomonas aeruginosa (Pa), screened out from the activated sludge of a petroleum refinery. We characterized the temporal variations in degradation efficacy for diesel and its five major constituents as a sole carbon source and identified more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 73 publications
0
13
0
2
Order By: Relevance
“…ANOVA test was performed to determine the significant differences in petroleum degradation efficiencies of three different consortia (p ≤ 0.05). SPSS ver.18 software (Chicago, IL, USA) was used to carry out the statistical analysis [28]. The tests of normality were assessed using Kolmogorov-Smirnov and Shapiro-Wilk analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANOVA test was performed to determine the significant differences in petroleum degradation efficiencies of three different consortia (p ≤ 0.05). SPSS ver.18 software (Chicago, IL, USA) was used to carry out the statistical analysis [28]. The tests of normality were assessed using Kolmogorov-Smirnov and Shapiro-Wilk analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, it was shown that K. pneumoniae had an effect on short-, medium-and longchain n-alkanes via enzyme systems and can be used in bioremediation studies [24]. However, You et al [28] clearly showed that K. pneumoniae only biodegraded hydrocarbons in the range of C 10 -C 14 in diesel. Zhou et al [30] reported that Pannonibacter phragmitetus was resistant to extreme environmental conditions such as hot springs, high alkaline conditions and high salt concentration and plays a role in the detoxification of PAHs and heavy metal chrome reduction in these environmental conditions.…”
Section: Biodegradation Of N-alkane Fractions In Petroleummentioning
confidence: 99%
“…Santiesteban-López & López-Malo, 2008;Belda-Galbis et al, 2011;Gupta et al, 2012;Tevatia et al, 2012; Mytilinaios et al, 2014;Pla et al, 2015; Ahmad et al, 2015;Ibrahim et al, 2018;Silva et al, 2018;You et al, 2018;Charlebois & Balázsi, 2019).…”
mentioning
confidence: 99%
“…The ratio of hydrophilic and hydrophobic moieties in the structure of biosurfactants will determine the degree of polarity and solubility of the biosurfactants in different solvent solutions. Glycolipids such as rhamnolipid and sophorolipid are typically extracted from aqueous solutions by standardised solvent extraction using ethyl acetate [46,48]. For instance, the crude sophorolipid from S. bambicola grown on glucose and refined, bleached, and deodorised (RBD) palm olein substrate has been successfully recovered by ethyl acetate with a total yield of 53.3 g/L [49].…”
Section: Recovery Of Biosurfactantmentioning
confidence: 99%
“…strain BS29, are effective in removing crude oil and PAHs from soil [60]. The rhamnolipid produced by P. aeruginosa Pa can reduce diesel by 58% in 14 days and degrade a higher carbon number of diesel constituents (C15 to C24) [48]. In another study, P.aeruginosa can degrade hydrocarbon components from C12 to C30, while Acinetobacter Iwoffii was more effective in degrading C11 to C17 hydrocarbon fractions than P.aeruginosa after 48 hours of incubation [61].…”
Section: Hydrocarbon Clean-up Processmentioning
confidence: 99%